The spirits of bad men made perfect : the life and diary of Confederate artillerist William Ellis Jones - Jones, Constance Hall, 1964- (Engaging the Civil War., 2020)
"The centerpiece of the book is the Civil War diary of William Ellis Jones, of Richmond, Virginia, who enlisted as an artillerist in Crenshaw's Battery, Army of Northern Virginia, just as the Confederate Conscription Act was coming into effect. Beyond the military interest, however, a thorough investigation into the diary's author."--Provided by publisher